Shock baby for the doctor - Hawkes, Charlotte (Hawkes, Charlotte. Billionaire twin surgeons., 2022)
A blast from the doctor's past... brings a baby into his future! Billionaire surgeon Basilius has just one rule: don't get attached! After a childhood where Bas was only every let down by those closest to him, he's hesitant to trust anyone. So why can't he stop thinking about nurse Naomi after four and a half months? Still, as Bas fights to forget her, he hits a stumbling block. Naomi is back as his new colleague -- and she's carrying his baby!